Программа выборочного магистерского курса “Экономическая социология” - Кульчицький, Б. (Социология: теория, методы, маркетинг, 2001)
The programme of optional course on “Economic Sociology” for MA students at the
Ivan Franko National University of L’viv.
Topic 1. The issue of economic sociology.
Topic 2. The methodology of economic sociology.
Topic 3. Categories and notions of economic sociology.
Topic 4. The classic theories of economic sociology.
Topic 5. The economic culture.
Topic 6. The sociology of human activity.
Topic 7. Economic motivation and types of rationality.
Topic 8. Problems of formation of the property institute.
Topic 9. Subjects of economic relations.
Topic 10. The sociology of labour market.
Topic 11. The sociology of economic systems.
Topic 12. The economic progress as active essence of a society.